Descriptive Study On The Teaching Reading Comprehension At The Sixth Grade Of Sd Al-Irsyad Surakarta In 2014/2015 Academic Year. - Pujilestari, Eni (2016)
This research aims to describing Descriptive Study on Teaching Reading Comprehension at the Sixth grade of Al-Irsyad Surakarta in 2014/2015. Learning English for students in Al-Irsyad seems less attractive, especially in reading, such as reading a narrative paragraph of text a long with question. The teacher must use the best method in the school level. This study is aimed at describe the learning process of reading comprehension in grade sixth from Al-Irsyad Surakarta in 2014/2015 and to classify the problem faced by English teacher in teaching reading sixth grade from Al-Irsyad. The type of the study is a descriptive research. The subject of the study is the English teacher and the sixth grade students of SD Al-Irsyad Surakarta. The object of the study is the process of teaching reading comprehension used by English teachers who teach elementary school students in the sixth grade SD Al-Irsyad Surakarta in 2014/2015 academic year. Data and data sources in this study are event, informant, and document. The writer collects the data by observation, interview, and document analysis. In method of collecting data, the writer does some ways to collect the data, such as doing observation, checking document, and doing interview with students and teacher. In analyzing data, the writer conducts some steps such as 1) collecting the data taken from observation and interview of the method used in teaching reading comprehension to the sixth grade students SD Al-Irsyad Surakarta, 2) analyzing the data from the result of observation and interview, 3) concluding the result and giving suggestion. The result of this research is the process of teaching reading comprehension divided into three procedures: pre-reading, whilst-reading and post-reading. Methods used by the English teacher are Direct Method, Grammar Translation Method, and Think Pair Share. Media used is textbook "Basic English and Lets Make Friends with English, white board, and dictionary. Evaluation system used by teacher are giving homework, giving practice, and questions-answer. Problem faced by the teacher are low students' interest, limitation of the students' vocabulary, and limitation of time. Problem solving used the teacher to overcome the problem is startegy to cope the low students' interest, strategy to cope the limitation of the students' vocabulary, and strategy to cope the limitation of time.